Pete the Kitty. Ready, set, go cart! - Dean, Kim, 1969-; Dean, James, 1957- (New York : Harper, 2021)
Pete the Kitty is excited to build his very own go-cart. But things don't go as planned. Turns out, his go-cart is missing a few important things. Thankfully, Bob and Gus are there to help Pete out!
0.8
K-3
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Cats -- Fiction; Karts (Automobiles) -- Fiction; Readers (Elementary); Animal fiction